Implementation of FAST Learning on Introductory Biology to Improve Science Process Skills on Madrasah Ibtidaiyah Teachers Prospective - Eni Setyowati (JPPIPA (Jurnal Penelitian Pendidikan IPA), 2020)
This research was aimed to determine the effectiveness of FAST (Fatonah, Amanah, Shidiq, Tabliq) learning on introductory biology to improve the science process skills on prospective Madrasah Ibtidaiyah teachers. The object of this research was 82 prospective of Madrasah Ibtidaiyah teachers. This research used the non-equivalent control group design. The instrument used esay test. Data analysis used the paired sample t-test, Mann Whitney, and the enhancement of science process skills used the gain score. The results showed that there was a significant increase in science process skills (sig. 0,00 < 0.05), in the high category. The enhancement of know what the job was 94% , very high category; can do the task completely was 87%, high category; the honesty was 98%, very high category; and the able to communicate was 86%, high category.